Assessment of Speaking Skills (Maharah Kalam) in Arabic Language Lesson at Madrasah Ibtidaiyah Riyadlus Sholihien Jember - Hakim, Tirto Luqmanul; Haris, Abdul; Huda, Mokhammad Miftakhul (Journal of Science and Education (JSE), 2025)
This study examines the Evaluation of Learning Speaking Skills (Maharah Kalam) in Arabic Subjects at Madrasah Ibtidaiyah Riyadlus Sholihien Jember. The purpose of this study was to understand how the implementation and evaluation techniques of learning speaking skills (Maharah kalam) in Arabic language lesson at Madrasah Ibtidaiyah Riyadlus Sholihien Jember. The research method used is descriptive qualitative with data analysis through documentation, observation, and interviews. After data collection, analysis was conducted to evaluate the study results. The research findings show that the learning of speaking skills (Maharah kalam) in Arabic language lesson at Madrasah Ibtidaiyah Riyadlus Sholihien Jember runs well. Teachers apply various methods such as singing to strengthen vocabulary memorization, The qowaid method, and translation. Although students are disciplined in terms of attendance, some students do not prepare learning equipment such as assignment books. The evaluation of speaking skill learning uses test and non-test techniques, where test techniques have been well implemented especially, in learning speaking skills but the implementation of non-test techniques is not optimal and depends on the initiative of the teacher.